THE RESPONSE OF MUSLIM YOUTH IN BANDA ACEH TOWARD ISLAMIC CONTEMPORARY ISSUES IN INDONESIA - Bustamam Ahmad, Kamaruzzaman; Ibrahim, Fitri Zulfidar; Shatilla, Qatrin Shabra (Islam Futura, 2025)
The study delves into the response of the younger generation of Muslims in Banda Aceh to contemporary issues in Indonesia. It aims to investigate their perspectives on religious tolerance and their attitudes towards socio-political issues in Indonesia. The author employed in-depth interviews and Focus Group Discussions (FGDs) to gain insights into the mindset of the young Muslim populace in Banda Aceh. The study unearthed a notable shift in the acquisition of religious knowledge, primarily through digital mediums, leading to a diminished association of violence and extremism with religious discord. The young Muslims of Banda Aceh exhibit a substantial inclination towards tolerance and nationalism. However, they hold firm in their unwillingness to compromise when tolerance undermines their religious convictions. Furthermore, they assert that national issues intertwined with Islam do not sway their overarching outlook on the nation and state.